Protease-activated receptor 2 deficient mice develop less angiotensin II induced left ventricular hypertrophy but more cardiac fibrosis. - Albrecht Meyer Zu Schwabedissen; Silvia Vergarajauregui; Marko Bertog; Kerstin Amann; Felix B Engel; Christoph Daniel (PLoS ONE)
Aims Activation of Protease Activated Receptor 2 (PAR2) has been shown to be involved in regulation of injury-related processes including inflammation, fibrosis and hypertrophy. In this study we will investigate the role of PAR2 in cardiac injury in a mouse model of hypertension using continuous infusion with angiotensin II. Methods Hypertension was induced in 12 weeks old wildtype (wt, n = 8) and PAR2 deficient mice (n = 9) by continuous infusion with angiotensin II for 4 weeks using osmotic minipumps. At the end, hearts were collected for analysis of left ventricular hypertrophy (LVH), myocardial capillary supply, fibrosis and localization of PAR2 expression using histological, immunohistological and mRNA expression analysis techniques. In addition, rat cardiac fibroblasts were treated with angiotensin II and PAR2 was inhibited by a blocking antibody and the PAR2 inhibitor AZ3451. Results Cardiac PAR2 mRNA expression was downregulated by 40±20% in wt mice treated with AngII compared to untreated controls. Four weeks after AngII treatment, LVH was significantly increased in AngII-treated wt mice compared to similarly treated PAR2-deficient animals as determined by relative heart weight, left ventricular cross-sectional area, and analysis of ventricular lumen area determined on sections. Treatment of wt mice resulted in an approximately 3-fold increase in cardiac expression of FGF23, which was 50% lower in PAR2-deficient animals compared to wt animals and therefore no longer significantly different from expression levels in untreated control mice. In contrast, cardiac interstitial fibrosis was significantly higher in PAR2-deficient mice compared to similar treated wt controls, as assessed by Sirius Red staining (>3-fold) and collagen IV staining (>2-fold). Additional experiments with isolated cardiac fibroblasts showed induction of pro-fibrotic genes when treated with PAR2 inhibitors. Conclusion In angiotensin II-induced cardiac injury, PAR2 deficiency has an ambivalent effect, enhancing fibrosis on the one hand, but reducing LVH on the other.